MINIMALLY INVASIVE FUNCTIONAL AESTHETIC RECONTOURING THROUGH SELECTIVE ENAMEL REDUCTION. A CASE REPORT - Sanabria, Pablo (2025)
Aesthetic dentistry is increasingly in demand by patients, in some cases, minimal modifications to the size, shape, or proportions of teeth are required, for which there are mainly direct or indirect additive techniques. Similarly, conservative dentistry seeks to meet aesthetic and functional objectives with minimal intervention. This clinical case describes a minimally invasive functional aesthetic recontouring with selective reduction of the enamel of the anterior teeth to optimize the aesthetic results of a 30-year-old male patient who consulted for an aesthetic improvement in the appearance of his smile. This technique offers advantages such as immediate results with aesthetic and functional benefits that can be considered economical and safe compared to conventional methods.